2013
DOI: 10.3920/bm2013.0017
|View full text |Cite
|
Sign up to set email alerts
|

A simulated mucus layer protects Lactobacillus reuteri from the inhibitory effects of linoleic acid

Abstract: Lactobacillus reuteri is a commensal, beneficial gut microbe that colonises the intestinal mucus layer, where it makes close contact with the human host and may significantly affect human health. Here, we investigated the capacity of linoleic acid (LA), the most common polyunsaturated fatty acid (PUFA) in a Western-style diet, to affect L. reuteri ATCC PTA 6475 prevalence and survival in a simulated mucus layer. Short-term (1 h) survival and mucin-agar adhesion assays of a log-phase L. reuteri suspension in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Following collection in Pyrex tubes, samples were stored at −80°C and freeze‐dried before extraction and methylation as described in De Weirdt et al . (). The sum of LA and its biohydrogenation products was calculated from the sum of LA, CLA, VA and SA (mg ml −1 ).…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…Following collection in Pyrex tubes, samples were stored at −80°C and freeze‐dried before extraction and methylation as described in De Weirdt et al . (). The sum of LA and its biohydrogenation products was calculated from the sum of LA, CLA, VA and SA (mg ml −1 ).…”
Section: Methodsmentioning
confidence: 97%
“…Devillard et al (2007) reported that LA increased the growth lag time of beneficial bacteria such as butyrate-producing and antiinflammatory Faecalibacterium prausnitzii, and lactic acid bacteria (LAB). Lactobacillus species were demonstrated to be highly sensitive to LA, as opposed to opportunistic pathogens such as Escherichia coli and Klebsiella pneumoniae (De Weirdt et al, 2013). However, survival of Lactobacillus reuteri upon LA exposure was improved when a mucosal environment was present (M-SHIME) (De Weirdt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations